632 SUTURED VERSUS MESH-AUGMENTED HIATUS HERNIA REPAIR: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS. (17th September 2021) - Petric, Josipa; Bright, Tim; Liu, David; Wee, Melissa; Watson, David
Abstract: : Repair of large hiatus hernias is increasingly being performed. However, there is no consensus for the optimal technique for hiatal closure between sutured versus mesh-augmented (absorbable or non-absorbable) repair. This meta-analysis systematically reviewed published randomized control trials (RCTs) comparing sutured versus mesh-augmented hiatus hernia (HH) repair. Our primary endpoint was HH recurrence at short- and long-term follow-up. Secondary endpoints were: surgical complications, operative times, dysphagia and quality of life. Methods: A systematic review of Medline, Scopus (which encompassed Embase), Cochrane Central Register of Controlled Trials, Web of Science and PubMed was performed to identify relevant studies comparing mesh-augmented versus sutured HH repair. Data were extracted and compared by meta-analysis, using odds ratio and mean differences with 95% confidence intervals. Results: Seven RCTs were found which compared mesh-augmented (non-absorbable mesh: n = 296; absorbable mesh: n = 92) with sutured repair (n = 347). There were no significant differences for short-term hernia recurrence (defined as 6–12 months, 10.1% mesh versus 15.5% sutured, P = 0.22), long-term hernia recurrence (defined as 3–5 years, 30.7% mesh vs 31.3% sutured, P = 0.69), functional outcomes and patient satisfaction. The only statistically significant difference was that the mesh repair required a longer operation time (P = 0.05, OR 2.33, 95% CI 0.03–24.69). Conclusion: Mesh repair for hiatus hernia does not offer any advantage over sutured hiatal closure. As both techniques deliver good and comparable clinical outcomes, a suture only technique is still an appropriate approach.